Intelligent remote/trigger : a photographer's buddy (Arduino based) - Wong, Wei Jun (2018)
High-speed photography is the art of capturing an image of rapid phenomena which is extremely fast for the human naked eyes to follow, like rock splashing into the water, rupture of water balloon burst, glass shattering and bullet fired. The process of using High-speed photography is to capture the exact moment to freeze the motion and reduced the motion blur. Photographer requires to be knowledgeable in the timing of the shutter and flash to capture this kind of high-speed image.